Goat Science Environment, Health and Economy - Kukovics, Sándor (IntechOpen, 2023)
This volume provides a comprehensive overview of goat keeping and farming. It includes twenty-two chapters that address such topics as breeding and selection, goat reproduction, production systems, the effects of goat farming on the environment, the use of goat byproducts, the economics of goat farming, and much more.